Red shirt color has no effect on winning in European Soccer: Reanalysis of Attrill et al. (2008) of the English premier league and six additional European leagues. (January 2022) - Goldschmied, Nadav; Furley, Philip; Trejo, Shakira; Haddad, Angela; Böning, Aaron
Abstract: Attrill et al. (2008) conducted a far-reaching study in elite English soccer demonstrating in archival research that from 1946 to 2003 seasons, teams wearing red uniforms were more likely to win championships than teams in other uniform colors, won more at home and had a higher average league position (relative to cross-city rivals). Their study was one of only very few that extended the color-in-context theory (Elliot & maier, 2007) to team, ball-oriented long-duration sports. The current investigation returns to the red superiority hypothesis in professional soccer due to weaknesses in the original evidence for this hypothesis. We conducted two studies testing the red superiority hypothesis in professional soccer. In Study 1a, we first reanalyzed the original data and tested the strength of evidence in favor of the red superiority hypothesis. We then updated the English premier league data (1992–2018) and tested uniform color effects on game outcomes. In Study 2, we attempted to broaden the scope of Study 1 and increase statistical power by testing the red superiority effect during the last 20 years of six major European Soccer leagues (NOS Portugal, German Bundesliga, Dutch Eredivisie, Spanish la Liga, French Ligue 1, and the Italian Serie A). All three tests challenge the validity of the original findings and fail to detect uniform color effects at home play in professional soccer. In light of the current findings and a growing body of research in the field we call into question overall color effects in this athletic context. Highlights: We reanalyzed the results of past research showing a red uniform colors superiority effect in English soccer. We found flaws in the original analyses and could not find the red superiority effect when more recent seasons were included. We extended the investigation to six elite European soccer leagues and, again, failed to detect the effect. We conclude that the effect detected by the original study is limited and most likely based on specious association.